A novel hybrid-honeycomb structure: Enhanced stiffness, tunable auxeticity and negative thermal expansion. (15th January 2021) - Peng, Xiang-Long; Bargmann, Swantje
Highlights: A novel hybrid-honeycomb structure with enhanced stiffness is proposed. It exhibits negative Poisson ratio and negative thermal expansion coefficient. Its effective thermoelastic properties are widely tunable. Analytical expressions of its effective thermoelastic constants are derived. Graphical abstract: Abstract: Most metamaterials with negative Poisson's ratio and/or negative thermal expansion coefficient possess relatively low stiffness. In this work, a novel hybrid-honeycomb structure with enhanced stiffness is proposed. It consists of two merged hexagonal honeycombs. Analytical and computational homogenization methods are used to evaluate the effective thermoelastic properties. Analytical expressions of the effective Young's modulus, Poisson's ratio, and thermal expansion coefficient are given. We show that the effective thermoelastic properties of the structure are widely tunable by tailoring the microstructural geometry and the constituent materials. In particular, the in-plane effective Poisson's ratio and thermal expansion coefficient are adjustable over a wide range, from negative to positive. By properly choosing the geometrical and material parameters, the structure can be designed to concurrently possess an enhanced stiffness and a high degree of auxeticity and negative thermal expansion.